2009
DOI: 10.1186/1471-244x-9-30
|View full text |Cite
|
Sign up to set email alerts
|

The posttraumatic stress disorder project in Brazil: neuropsychological, structural and molecular neuroimaging studies in victims of urban violence

Abstract: Background: Life trauma is highly prevalent in the general population and posttraumatic stress disorder is among the most prevalent psychiatric consequences of trauma exposure. Brazil has a unique environment to conduct translational research about psychological trauma and posttraumatic stress disorder, since urban violence became a Brazilian phenomenon, being particularly related to the rapid population growth of its cities. This research involves three casecontrol studies: a neuropsychological, a structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 84 publications
0
20
0
1
Order By: Relevance
“…Other studies have already suggested that dopamine plays an important role in the pathogenesis of PTSD (Comings et al 1996;Segman et al 2002;Bressan et al 2009). …”
Section: Discussionmentioning
confidence: 95%
“…Other studies have already suggested that dopamine plays an important role in the pathogenesis of PTSD (Comings et al 1996;Segman et al 2002;Bressan et al 2009). …”
Section: Discussionmentioning
confidence: 95%
“…Other measures requiring inhibition of responses include the go-nogo, stop-signal, and attention network (ANT) tasks (Logan, 1994; Shucard , et al 2008; Jenkins , et al 2000; Fan , et al 2002). Decreased inhibitory function has rather consistently been reported for PTSD (Falconer , et al 2008; Wu , et al 2010; Koso and Hansen 2006; Casada and Roache 2005; Shucard , et al 2008; Bressan , et al 2009; Jenkins , et al 2000; Leskin and White 2007), and performance has been reported to relate to PTSD symptom severity (Falconer , et al 2008; Leskin and White 2007). The color-word Stroop task (Stroop, 1935; Delis , et al 2001) examines response time to name the ink color of a color-related word (e.g., “red” printed in blue ink) and is also thought to be a measure of inhibitory function.…”
Section: Attention Working Memory and Executive Function In Ptsdmentioning
confidence: 92%
“…Due to an expected refusal rate of 20%, and in order to increase the likelihood of identifying post-traumatic stress disorder cases, the three strata with the highest homicide rates were oversampled, resulting in 1500 interviews. In Sao Paulo, we expected to identify approximately 120 current cases to be referred to a case-control study [23] and to a clinical trial [24] on post-traumatic stress disorder (PTSD). As we expected a 5% one-year prevalence of PTSD, we decided to increase the sample size to 3,000 interviews to allow for the identification of the required PTSD cases.…”
Section: Methodsmentioning
confidence: 99%